Transformation of Inquiry Learning Utilizing Lake Tondano Environment to Enhance Students' IPAS Learning Outcomes - Kalengkongan, Jeane; Umboh, Deane (Jurnal Ilmiah Wahana Pendidikan, 2025)
The persistently low IPAS (Science and Social Studies) learning outcomes among elementary school students necessitate serious attention in educational practices. This study aimed to investigate the effectiveness of an inquiry learning model utilizing the Lake Tondano environment in enhancing the IPAS learning outcomes of fifth-grade elementary school students. Employing a quasi-experimental design with a pretest-posttest non-equivalent control group, the research utilized objective tests and learning activity observation sheets as instruments, both of which had undergone validation. The findings indicate that the inquiry learning model leveraging the Lake Tondano environment significantly improved students' IPAS learning outcomes. Students participating in this learning demonstrated enhanced understanding of ecosystem concepts and critical thinking skills, alongside increased awareness of environmental issues. This learning model proved effective not only in boosting IPAS achievement but also in providing a more profound and immersive learning experience for students.